Question
upstudy study bank question image url

\[ P(x)=x^{4}+9 x^{3}+17 x^{2}-9 x-18 \] Write the polynomial in factored form. \( P(x)=\square \)

Ask by Ford Love. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( P(x) = (x - 1)(x + 1)(x + 3)(x + 6) \)

Solution

To factor the polynomial   P(x) = x⁴ + 9x³ + 17x² – 9x – 18 follow these steps: 1. Find a root by testing small integers. Try x = 1:   P(1) = 1 + 9 + 17 – 9 – 18 = 0 Since P(1) = 0, (x – 1) is a factor. 2. Divide P(x) by (x – 1). Using synthetic division with coefficients 1, 9, 17, –9, –18:   • Bring down 1.   • Multiply 1 by 1 and add to 9 to get 10.   • Multiply 10 by 1 and add to 17 to get 27.   • Multiply 27 by 1 and add to –9 to get 18.   • Multiply 18 by 1 and add to –18 to get 0. The quotient is x³ + 10x² + 27x + 18. 3. Factor the cubic quotient: x³ + 10x² + 27x + 18. Test x = –1:   (–1)³ + 10(–1)² + 27(–1) + 18 = –1 + 10 – 27 + 18 = 0 So, (x + 1) is a factor. Using synthetic division for the cubic with root –1 (coefficients: 1, 10, 27, 18):   • Bring down 1.   • Multiply 1 by –1 and add to 10 to get 9.   • Multiply 9 by –1 and add to 27 to get 18.   • Multiply 18 by –1 and add to 18 to get 0. The quadratic quotient is x² + 9x + 18. 4. Factor the quadratic: x² + 9x + 18 factors as (x + 3)(x + 6) because 3 + 6 = 9 and 3 · 6 = 18. 5. Combine all factors:   P(x) = (x – 1)(x + 1)(x + 3)(x + 6). Thus, the factored form of the polynomial is:   P(x) = (x – 1)(x + 1)(x + 3)(x + 6).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To factor the polynomial \( P(x) = x^{4} + 9x^{3} + 17x^{2} - 9x - 18 \), we can start by looking for rational roots using the Rational Root Theorem. After testing a few values, we find that \( x = -2 \) is a root. Using synthetic division, we can divide \( P(x) \) by \( x + 2 \), which gives us \( P(x) = (x + 2)(x^{3} + 7x^{2} + 7x - 9) \). Next, we can seek to factor the cubic polynomial \( x^{3} + 7x^{2} + 7x - 9 \). After trying more roots, we find that \( x = 1 \) is also a root. Dividing again, we eventually factor it down further, giving us: \[ P(x) = (x + 2)(x - 1)(x^2 + 8x + 9) \] The quadratic can be factored to give: \[ P(x) = (x + 2)(x - 1)(x + 3)(x + 3) \] So, we can write: \[ P(x) = (x + 2)(x - 1)(x + 3)^2 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy